Routing techniques for millimetre wave communications. (2nd June 2023) - Alanazi, Faisal
In this paper, we propose three routing protocols for millimetre wave communications. One-hop routing protocol (OHRP) consists to choose the best relay in each hop. Optimal routing protocol (ORP) consists to activate the path with the best signal to interference plus noise ratio (SINR) among all available N L -1 paths where N is the number of branches (number of relays in each hop) and L is the number of hops. Suboptimal routing protocol (SORP) splits the network in K subnetworks then the best path is activated in each subnetwork. Our analysis is valid for millimetre wave communications in the presence of P interferers at each relay node.